HUBUNGAN PARTUS LAMA DENGAN KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR DI UPT PUSKESMAS WATAMPONE - Mustar (Jurnal Suara Kesehatan, 2021)
Abstract. Newborn asphyxia can be associated with several conditions of pregnancy and birth. The baby is in a high-risk state and the mother is in a high-risk pregnancy. At the age of 30 weeks of gestation, the fetal lungs have shown maturation both anatomically and functionally, although the fetus does not carry out respiratory movements unless there is a disturbance that can cause hypoxia / anoxia. In the asphyxia state, the baby is deficient in O2 and excess CO2 which can lead to acidosis. This condition is the cause of failure to adapt and often progresses to respiratory distress syndrome and in the first days of birth.To know the relationship between old labor and the incidence of asphyxia in newborns at the UPT Puskesmas Watampone.The type of research used in this study was an analytic survey with a cross sectional study design. So that the number of samples that meet the criteria is determined as many as 20 people.The results showed that there was a relationship between prolonged labor and the incidence of asphyxia in newborns, with the chi square test value obtained p-value = 0.001 p <0.05. Of the 20 respondents, the highest was found in the category of non-labor for a long time and did not experience asphyxia as many as 13 respondents (65%). While the lowest was in the category of prolonged labor and not experiencing asphyxia as many as 2 respondents (10%). Conclusion: There is a relationship between prolonged labor and the incidence of asphyxia in newborns at the UPT Puskesmas Watampone